Optimasi Metode Ekstraksi Terhadap Parameter Mutu Ekstrak Daun Ketepeng Cina (Senna alata) - Nuryati Nuryati; Raden Rizki Amalia; Nina Hairiyah; Nanis Nurisyah (Jurnal Teknologi Agro-Industri, 2023)
Ketepeng Cina (Cassia alata) is a plant that is widely used to treat various skin problems caused by bacteria or fungi. Various studies have been carried out to obtain optimal extract results such as the influence of the type of drying or solvent used. The optimal extract can be used for applications in making products based on Chinese ketepeng extract such as gel, cream or soap preparations. In this research, optimization of the extraction method will be carried out to obtain extracts with the best parameters in terms of water content, yield and flavonoid values ​​resulting from extraction methods using cold methods (maceration) and hot methods (sochlet and reflux). The research results showed that the optimal extract produced was using the reflux method with a yield value of 23,24%, water content of 4,02%, total ash content of 1,20%, non-acid ash content of 1,04%, and flavonoids of 8,78%.